Eadeward Muybridge motion studies (The Voyager Company, 1990)
Through modern technology a method for comprehensive examination of Muybridge's pioneering work in the history of motion study is offered on this videodisc. He was the first director of motion pictures. As an innovative photographer, he was able to solve considerable problems of photographic practice in an era when a photographer had to be at least a passable chemist and inventor. His photographic sequences are the most comprehensive and important studies of human and animal movement in the history of motion pictures.